Trajectory of Indo Political Movements and Indis Nationalism in the Dutch East Indies - Nugroho, Khairana Zata; Ramadhan, Fauzan Syahru; Daradjati, Keke Pahlevi; Susanti, Desi (Analisis Sejarah, 2025)
This study examines the Indo political movements in the Dutch East Indies during the early 20th century, focusing on the Indische Partij and Insulinde organizations and their quest for Indis nationalism. Using a historical method and sociological approach, particularly Neil J. Smelser's theory of collective behavior, this study analyzes the Indo community's role in the Indonesian national movement. The implementation of the Dutch Ethical Policy, which produced nationalist intellectuals among indigenous people, and the strengthening of racial segregation in the Dutch East Indies, led to concerns among the Indo community. E. F. E. Douwes Dekker, concerned about Indo people as Indiers, developed the concept of Indiers and Indis nationalism through the organization known as the Indische Partij. The formation of Indische Partij then sparking collective behavior to oppose the Dutch East Indies government in the form of political activism. Together with Soewardi Soerjaningrat and Tjipto Mangoenkoesoemo, they were known as Tiga Serangkai and helped mobilizing the Indische Partij masses to fight for freedom from Dutch control and helped mobilizing the Indische Partij masses to fight for freedom from Dutch control. The Indische Partij disbanded after the Dutch East Indies government deemed it subversive and exiled the Tiga Serangkai. The Insulinde organization emerged as the Indische Partij's successor, with Douwes Dekker and Tjipto participating. However, the Dutch East Indies government's rejection of Insulinde's legal application led to its dissolution and signaled a turning point in the trajectory of Indis nationalism.